Design of mass burial sites for safe and dignified disposal of pandemic fatalities. Issue 3 (5th January 2021) - Leong, Eng-Choon; Abuel-Naga, Hossam; Goli, Venkata Siva Naga Sai; Jha, Bhagwanjee; Pathak, Pankaj; Singh, Devendra Narain
Abstract : The huge number of fatalities due to the coronavirus disease 2019 pandemic has imposed an unprecedented pressure on existing burial facilities. Thus, mass burial is being used in different parts of the world to cope with this unusual situation. As a dead body might be contagious for at least hours, if not days, there is a need to manage/design/construct the mass burial considering the safe handling of coffins and other environmental, social, economical and ethical/dignity aspects. However, the guidelines of the World Health Organization do not thoroughly address the potential risk associated with groundwater pollution due to mass burial construction. Hence, the present study discusses the potential risk of groundwater pollution in mass burial sites and sheds light on the factors that control the survival/retention of bacteria and viruses in porous media. Furthermore, using the available knowledge on designing/monitoring of municipal/industrial waste disposal sites, a cost-effective and simple construction method of mass burial is proposed to mitigate its potential environmental impact.